2014
DOI: 10.2147/dmso.s36455
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and sexual dysfunction: current perspectives

Abstract: Diabetes mellitus is one of the most common chronic diseases in nearly all countries. It has been associated with sexual dysfunction, both in males and in females. Diabetes is an established risk factor for sexual dysfunction in men, as a threefold increased risk of erectile dysfunction was documented in diabetic men, as compared with nondiabetic men. Among women, evidence regarding the association between diabetes and sexual dysfunction are less conclusive, although most studies have reported a higher prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
119
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 133 publications
2
119
0
7
Order By: Relevance
“…This could be due to the fact that subjects with a lower BMI are more confident in solving their problem and, therefore, more frequently seek medical care for their sexual difficulties. We also found that diabetes mellitus is a predictor for lack of referral, even if significantly associated with FSD (see [27,28] and present study). Similarly, subjects suffering from hypertension or with a medical history of bariatric surgery were more likely to have FSD, but also to refrain from referring.…”
Section: Discussionsupporting
confidence: 78%
“…This could be due to the fact that subjects with a lower BMI are more confident in solving their problem and, therefore, more frequently seek medical care for their sexual difficulties. We also found that diabetes mellitus is a predictor for lack of referral, even if significantly associated with FSD (see [27,28] and present study). Similarly, subjects suffering from hypertension or with a medical history of bariatric surgery were more likely to have FSD, but also to refrain from referring.…”
Section: Discussionsupporting
confidence: 78%
“…Less research is available regarding sexual health for males, particularly in youth; however, males with diabetes have a threefold increased risk of erectile dysfunction compared with men who do not have diabetes (106,107). Open and factual discussions of these topics facilitate future comfort in disclosing any concerns regarding sexual function.…”
Section: Life Course Considerationsmentioning
confidence: 99%
“…However among the women the evidence of the association of diabetes mellitus and sexual dysfunction is less conclusive even though most studies have reported higher prevalence of female sexual dysfunction in diabetic women when compared with non-diabetic women. In men diabetes mellitus is an established risk factor for sexual dysfunction with a documented threefold increase in risk of erectile dysfunction in diabetes mellitus men comparing to non-diabetes mellitus men (Esposito, Maiorino, and Bellastella 2014). In this study the prevalence of erectile dysfunction was high and more than 55. sexual disorders are considered personal and private that most patients will not readily discuss them (Unadike, Eregie, and Ohwovoriole 2008).…”
Section: Discussionmentioning
confidence: 58%
“…However it has been reported that it is not clear whether hyperglycaemia is a risk factor for the development of erectile dysfunction. Some studies have observed association between poor glycaemic control as expressed by elevated levels of glycosylated haemoglobin whist other studied did not report any association (Esposito, Maiorino, and Bellastella 2014). Further research is required to clarify causal link between prolonged hyperglycaemia and erectile dysfunction (Binmoammar et al 2016).…”
Section: Discussionmentioning
confidence: 97%